Determinants of menarche - Papadimitriou Anastasios; Karapanou Olga (BMC, 2010)
Abstract Menarche is a milestone in a woman's life as it denotes the start of reproductive capacity. Aim of this report is to review the recent developments and the current knowledge in the neuroendocrinology of pubertal onset and the factors, genetic and environmental, that influence menarcheal age. We also review the implications of early or late menarcheal age on a young woman's life.